(2-a)(2+a)=-(a-2)(2-a) Or (2-a)(2+a)=-[(a-2)(2-a)] Or (2-a)(2+a)=-(a-2)*-(2-a) Which of these would be correct?
Follow Math Help Forum on Facebook and Google+
Originally Posted by Beetle (2-a)(2+a)=-(a-2)(2-a) Or (2-a)(2+a)=-[(a-2)(2-a)] Or (2-a)(2+a)=-(a-2)*-(2-a) Which of these would be correct? none are correct. $\displaystyle (2-a)(2+a) = -(a-2)(2+a)$
(2-a)(2+a)=-[(a-2)(-2-a)] Or (2-a)(2+a)=-(a-2)*-(-2-a) What about this?
Originally Posted by Beetle (2-a)(2+a)=-[(a-2)(-2-a)] Or (2-a)(2+a)=-(a-2)*-(-2-a) What about this? seems like you're guessing here. check by substituting a value in for $\displaystyle a$ to see if the factorization works.
View Tag Cloud